Nominal Forms of Address and their Pragmatic Functions in Arab Society in the Era of Prophet Muhammad PBUH through Sīratu ibni Hishām; A Sociolinguistic Study - Alhasan, Muhammed Muvaffak; Mohammad Dello, Ahmad (Dirasat: Human and Social Sciences, 2024)
Objectives: This study sought to investigate the nominal forms of address in the Arab society during the Prophet Muhammad's era through the book sīratu ibni Hishām. Methods: The research selected Ibn Hisham's biography as a sample for the study. It analyzed the various forms of address found in the text using theoretical perspectives such as power/solidarity, intimacy/distance, and politeness. Furthermore, the study highlighted the role of social variables, such as age, gender, and social status, in the selection of forms of address. Results: The research concluded that the variables of age and social status played a role, albeit limited to specific social contexts, in determining the choice of forms of address. However, regarding gender, the study's sample did not provide sufficient evidence to draw a convincing conclusion. Conclusions: The research demonstrates that the selection of forms of address in many instances within the sample was not random; rather, it was purposeful and employed pragmatically with the aim of influencing communication outcomes.